Loyalty Of The Main Character In The Choice Movie Directed By Ross Katz - Unpris Yastanti (Wanastra: Jurnal Bahasa dan Sastra, 2019)
Abstract- The purpose of this analysis is to identify loyalty of the main character in The Choice movies. This study used descriptive qualitative method to analyze the data. The data are the scenes and the dialogs of the main character that contains loyalty. The results of this research indicates that;(1)  The loyalty appears in the main character, (2) The loyalty types of the main character are romantic loyalist and loyal sentinel, (3) the moral message contained in the movie are keep loyal and strong, never give up, and always together that this movie explains clearly that to be a true man is one of the condition that must be possessed is loyalty.     Keywords:  literature, main character, types of loyalty.